Modeling hysteresis in the phase transition of industrial-grade solid/liquid PCM for thermal energy storages - Barz, Tilman; Sommer, Andreas (International journal of heat and mass transfer, 2018)
Latent heat storages using phase change materials (PCM) ideally store and release heat at an almost constant, unique temperature. However, most in-dus-tri-al-grade solid/liquid PCM melt and solidify over a temperature range in which both phases coexist, and hysteresis in the phase transition sometimes significantly increases this non-ideal behavior. Models which can reproduce non-ideal phase transitions are crucial for the numerical analysis of the charging and discharging of latent heat storages. Not only the PCM thermophysical properties strongly change during phase transition, but also the heat transfer critically depends on melting and solidification temperatures. This contribution focuses on phenomenological and macroscopic modeling approaches to account for hysteresis in the temperature induced phase transition of industrial-grade PCM. It is assumed that the PCM structure can be approximated by two phases: solid and liquid, and that phase transitions take place over a temperature range in which both phases coexist. Starting from a standard model, a rate-independent static hysteresis model is derived which can be directly parametrized using data from Differential Scanning Calorimetry (DSC). In addition, two rate-dependent models are considered. These models reproduce dynamic hysteresis and are indirectly parametrized by fitting macrokinetic models to experimental data. All models produce very different evolutions of the phase fractions during melting and solidification. The models are linked to a 2D energy balance equation model of a lab-scale latent heat storage. Recorded temperatures confirm that the phase transitions of the applied PCM are significantly affected by hysteresis phenomena. Whereas the standard model is incapable to reproduce these phenomena, it turns out that the static hysteresis model and both macrokinetic models show qualitatively very convincing results. These findings are discussed for alternating storage operation (multiple successive melting and solidification cycles) including incomplete phase transitions and direction changes at arbitrary points therein.
Gesehen am 05.03.2020